(untitled) (Colombia Medica, 2007)
Background: «Syndrome X», known since the 1980’s is a disease condition precipitated by insulin resistance. Insulin resistance causes glucose and insulin to accumulate in the blood. Syndrome X is characterized by abnormal values of triacylglycerol (TAG), blood pressure (BP), glucose and HDL-cholesterol-all risk factors for heart disease. Insulin resistance may be exacerbated by bad diet, poor lifestyle, absence of physical activity, genetic predisposition and being overweight. However, recent reports have shown that poor lifestyle is likely to be the main cause rather than bad diet or being overweight. Even though heavy consumption of alcohol could be regarded as a poor lifestyle, its relationship to the biochemical features and symptoms of Syndrome X in both genders is yet to be properly documented among Nigerian drinkers of alcohol. Methods: To establish a baseline information on the relationship between alcohol consumption and Syndrome X among Nigerians, two hundred and seventy-four consenting individuals in apparent good health and who were either light (53 male, 44 female), moderate (51 male, 42 female) or heavy (46 male, 38 female) drinkers of alcohol were selected. They had no personal or familial history of CHD, stroke, cancer or related diseases. The drinkers were tested using an acute dose (1 g ethanol/kg body weight) of alcohol. Results: Results show that the administered acute dose (1 g ethanol/kg body weight) increased serum glucose, (p>0.05), TAG (p< 0.05) and BP (p< 0.05) some biochemical risk factors of Syndrome X in both genders irrespective of the drinking category. However, alcohol-induced changes were highest among the female heavy drinkers. Thus, observations from this study suggest that heavy consumption of alcohol by especially the female folk could alter the pathways that metabolize carbohydrates and lipids and this may increase the risk of Syndrome X. Conclusions: Based on the available evidence, it would be reasonable to conclude that heavy consumption of alcohol by Nigerian women especially may be yet another predisposing lifestyle to Syndrome X. The incidence of Syndrome X among drinkers of alcohol should be further investigated in order to provide clues to the underlying molecular mechanisms. This is important in order to strategize therapeutic approaches, since individuals with the disease may not recognize it.